Turning the Co-Production Corner: Methodological Reflections from an Action Research Project to Promote LGBT Inclusion in Care Homes for Older People - Willis, Paul (Int J Environ Res Public Health, 2018)
Background: Older lesbian, gay, bisexual and trans (LGBT) residents are often invisible in long-term care settings. This article presents findings from a community-based action research project, which attempted to address this invisibility through co-produced research with LGBT community members. Particular Question: What conditions enable co-produced research to emerge in long-term residential care settings for older people? Aims of Project: To analyse outcomes and challenges of action-oriented, co-produced research in the given context. In particular, we explore how co-production as a collaborative approach to action-orientated research can emerge during the research/fieldwork process; and reflect critically on the ethics and effectiveness of this approach in advancing inclusion in context. Methods: The project was implemented across six residential care homes in England. Reflections are based on qualitative evaluation data gathered pre- and post-project, which includes 37 interviews with care home staff, managers and community advisors (two of whom are co-authors). Results and Conclusions: We discuss how the co-production turn emerged during research and evaluate how the politics of this approach helped advance inclusion—itself crucial to well-being. We argue for the value of co-produced research in instigating organizational change in older people’s care environments and of non-didactic storytelling in LGBT awareness-raising amongst staff.